2015
DOI: 10.1186/s12872-015-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute coronary syndromes in a developing country; time for a paradigm shift? an observational study

Abstract: BackgroundThere are limited contemporary data on the presentation, management and outcomes of acute coronary syndromes (ACS) in Sri Lanka. We aimed to identify the critical issues that limit optimal management of ACS in Sri Lanka.MethodsWe performed a prospectively observational study of 256 consecutive patients who presented with ACS between November 2011 and May 2012 at a tertiary care general medical unit in Sri Lanka.ResultsWe evaluated data on presentation, management, in-hospital mortality, and major adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 21 publications
2
39
1
Order By: Relevance
“…The proportion of patients thrombolysed ( n = 356/505, 70.5%) compares well or is even better than in other developing countries. In Sri Lanka, 70.2% of STEMI patients receive thrombolysis [23], 41% of STEMI patients in India [24], 44.7% in Cape Town [18], 59% in Iran [25], 62% in Kenya [26] and 27% at a tertiary-care hospital in Sri Lanka [27]. Our study also compares well with studies from first world countries such as Scotland [28].…”
Section: Discussionsupporting
confidence: 70%
“…The proportion of patients thrombolysed ( n = 356/505, 70.5%) compares well or is even better than in other developing countries. In Sri Lanka, 70.2% of STEMI patients receive thrombolysis [23], 41% of STEMI patients in India [24], 44.7% in Cape Town [18], 59% in Iran [25], 62% in Kenya [26] and 27% at a tertiary-care hospital in Sri Lanka [27]. Our study also compares well with studies from first world countries such as Scotland [28].…”
Section: Discussionsupporting
confidence: 70%
“…It was observed that the STEMI: NSTEMI ratio was approximately 1: 5. This is an exaggeration of the documented local prevalence mentioned by Medagama and others in 2015 [ 8 ]. It is, however, on par with the current trend of European countries and in contrast to the prevalence recorded in some African countries [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 84%
“…Coronary heart disease has been a burden for developed countries as well as for developing countries [ 3 7 ]. Sri Lanka, being a LMI country, suffers from the consequences of these cardiovascular diseases [ 8 ]. Myocardial Infarction (MI) is one of the main acute critical effects which reflect the tip of the iceberg of chronic NCDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the United States alone suggest that approximately 0.55 million first episodes and 0.2 million repeated episodes of acute MI occur annually [8], while 15 million people suffer from stroke worldwide with five million deaths and leaving another five million permanently disabled annually [9]. Together, MI and stroke have affected large numbers of people around the world [10][11][12] including Korea [13].…”
Section: Introductionmentioning
confidence: 99%